Determinants of risk reporting by portuguese and spanish non-finance companies - Oliveira, J. (2018)
Purpose – The paper seeks to assess the risk reporting practices across two European Latin countries (Portugal and Spain). Moreover, drawn on elements of agency, legitimacy, resources-based perspectives, and institutional theory this study also intends to assess if the influence of corporate governance mechanisms on risk reporting is mediated by strategic/institutional legitimacy interests. Design/methodology/approach – From a sample of 60 non-finance Portuguese and Spanish companies with securities traded on the Euronext Lisbon stock exchange market and on the Madrid stock exchange market, respectively, at December, 2011, the Corporate Governance reports and the “risk/risk management” sections of the Management reports included on consolidated annual reports for 2011 were manually content analyzed, according to prior literature. Further, multiple linear regressions were used to assess the potential relationships between corporate governance mechanisms and risk reporting. Findings – Results indicate that visible companies, operating in a country with a weaker legal environment, and during periods of financial distress disclose more discretionary RRD, basically to contextualize their negative outcomes. Some corporate governance mechanisms were crucial to improve risk information. Originality – The paper goes beyond prior literature work and assesses if the theoretical framework grounded on agency, legitimacy, resources-based perspective, and institutional theory is suitable in explaining RRD in an under-researched setting (European Latin countries, such as Portugal and Spain with low agency costs and different corporate governance models). Moreover, the analysis embraces a wider and homogeneous range of internal and external corporate governance mechanisms and uses a period in which both countries were severely affected by a sovereign debt crisis with negative impacts on company’s liquidity and financial risks. A research setting like this has not been studied hitherto.